Detection of glyco-mucin profiles improves specificity of MUC16 and MUC1 biomarkers in ovarian serous tumours - Ricardo, Sara (2017)
Support by Programa Operacional Ciencia e Inovacao 2010 do Quadro Comunitario de Apoio III and FEDER (PTDC/SAU-ONC/117216/2010). IPATIMUP is an Associate Laboratory of the Portuguese Ministry of Science, Technology and Higher Education and partially supported by FCT. Project NORTE - 07-0124-FEDER-000024 co-financed by Programa Operacional Regional do Norte (ON.2 - O Novo Norte), under Quadro de Referencia Estrategico Nacional (QREN), by Fundo Europeu de Desenvolvimento Regional (FEDER). Lara Marcos-Silva acknowledges also FCT for financial support through a PhD fellowship (SFRH/BD/60536/2009). Support by Kirsten og Freddy Johansen Fonden, A.P. Moller og Hustru Chastine McKinney Mollers Fond til Almene Formaal, The Novo Nordisk Foundation, The Danish Research Councils, a programme of excellence from the University of Copenhagen, and The Danish National Research Foundation (DNRF107).